Predictor factor of telecentres outcome from the users perspectives in rural communities - Badsar, Mohammad; Abu Samah, Bahaman; Abu Hassan, Musa; Osman, Nizam; Mohd Shaffri, Hayrol Azril (American-Eurasian Network for Scientific Information, 2011)
Problem statement: Information and Communication Technologies (ICTs) in developing countries is considered as a fundamental strategy of community development. In this regard, the government of Malaysia and developing agencies considered telecentres as a tool for providing the potential and benefits of ICTs for rural and remote community in order to make value and offer equal ICT access to all Malaysians and to transform Malaysia into a value based Knowledge Society by the year 2020. However, the lack of success and sustain ability is a common problem for telecentre projects that cause increasing necessity for paying more con sideration to extract lessons learned of projects, with particular attention to factors influence tele centre outcomes which is the aim of this study. Approach: the main purpose of this study was to define the predictor factors of telecentres outcomes from user’s perception in rural communities in Malaysia. A cross sectional survey method was employed in the study and data were collected from 360 respondents who were randomly selected from the Pusat Internet Desa (PID) and Medan InfoDesa (MID) centers. For the purpose of analysis, Structural Equation Modeling (SEM) by AMOS software was used. Result: The results of the Structural Equation Modeling (SEM) analyses show that individual characteristics, telecentres characteristics, information characteristics and leadership competency variables had significant contribution toward the prediction of telecentre outcome. Also the results showed that the information characteristic variable had better contribution toward the prediction of telecentre outcomes in rural community. Conclusion: based on highest contribution of the information characteristics among investigated factors, it could be concluded that any efforts must be made to improve service quality and provide relevant content to respondent needs in local language. Thus, access to local and relevant content can play a critical role in stimulating the users in rural community to have a continuous connection with telecentres and finally achieving desire outcome.